The effect of vitamin D on clinical manifestations and activity of Behçet’s disease - Aslan, Nurşad; Demirci, Kamile; Güler, Tuba; Dörtbaş, Fulya; Kale, Ebru (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Immune mechanisms have been implemented to have a role in the pathogenesis of Behçet’s disease (BD) and vitamin D has been shown to have a regulatory role in the immune system function. Aim: To evaluate the vitamin D levels of BD patients and its relationship between clinical findings and disease activity of BD. Material and methods: Sixty-eight patients with BD and 70 age- and sex-matched controls were examined retrospectively. Demographic features, vitamin D levels for both groups and clinical findings, disease activity, drug usage for BD patients were examined from their medical reports. Disease activity was calculated for each patient according to Krause’s BD activity assessment. Results: Mean vitamin D levels of patients and controls were 15.35 ±7.18 ng/ml and 18.44 ±5.79 ng/ml, respectively. Vitamin D levels were significantly lower in BD patients than in controls (p = 0.006). Mean vitamin D levels of active and inactive BD cases were 15.68 ±7.31 ng/ml and 15.08 ±7.17 ng/ml, respectively (p = 0.73). Disease activity of patients using and not using vitamin D was similar (p = 0.51). Conclusions : Significantly lower levels of vitamin D were observed in BD patients. Our results indicate that there is no correlation between BD activity and a vitamin D level. Together with these, vitamin D replacement treatment was found to have no effect on disease activity.